2017
DOI: 10.1097/md.0000000000008157
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of kinematic and mechanical alignment techniques in primary total knee arthroplasty

Abstract: Background:This meta-analysis compared clinical and radiographic outcomes and complications of kinematic alignment (KA) and mechanical alignment (MA) techniques in primary total knee arthroplasty (TKA).Methods:All studies comparing the operation time, change in hemoglobin, length of hospital stay, postoperative complications, and clinical and radiographic outcomes as assessed with various measurement tools, from direct interview to imaging methods, in patients who underwent primary TKA through the KA or MA tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
25
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 31 publications
4
25
0
1
Order By: Relevance
“…Our meta‐analysis revealed that the rate of ligament release in MA‐TKA was higher than that in KA‐TKA ( P = 0.0008). Consistent with findings in previous studies 27, 31, 33, 36, 38–40 , we found that the KA‐TKA group had better knee function outcomes than the MA‐TKA group in terms of the WOMAC score, KSS, combined KSS, and KSS.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our meta‐analysis revealed that the rate of ligament release in MA‐TKA was higher than that in KA‐TKA ( P = 0.0008). Consistent with findings in previous studies 27, 31, 33, 36, 38–40 , we found that the KA‐TKA group had better knee function outcomes than the MA‐TKA group in terms of the WOMAC score, KSS, combined KSS, and KSS.…”
Section: Discussionsupporting
confidence: 92%
“…While relevant meta‐analyses have been published in recent years, these studies included randomized controlled trials, case reports, and systematic reviews 27, 31 . Two systematic reviewss 27, 31 have analyzed the kinematic and mechanical alignment techniques in TKA. These two meta‐analysess 27, 31 included retrospective observational studies and randomized controlled trials (RCTs).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meta-analysis compared the clinical and radiographic outcomes and complications between the KA and MA techniques in primary TKA and showed no significant differences in postoperative complications. The overall functional outcome was better in KA than in MA [49].…”
Section: Discussionmentioning
confidence: 79%
“…Also, kinematically aligned TKA might address some of the aforementioned topics. However, clinical benefit still is controversially discussed [25,28,29] and because it is recommended to use computer navigation or patientspecific instruments to ensure accuracy, it likely adds cost to the procedure. Although our findings may suggest that additional releases likely are needed with off-the-shelf designs to address the anatomic differences between implant sizes and patients' anatomies, and these soft tissue releases may weaken supportive knee ligaments, there is no robust evidence of which we are aware that this results in compromises to pain relief or function.…”
Section: Discussionmentioning
confidence: 99%